No School For Eze - Okoye, Ifeoma (Nigeria, 2007)
Eze did not like school. One morning when it was time for Eze to go to school, he began to cry. ''Mummy, let me stay at home with you today,'' Eze said. ''No Eze, you should go to school and learn and write,'' Mummy said.
Keywords: Family; Juvenile Fiction